2019
DOI: 10.15514/ispras-2019-31(3)-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of а software framework for real-time management of intelligent devices

Abstract: The subject of this paper is development of software framework for real-time management of intelligent devices. The framework enables intelligent management of IoT devices in cyber-physical systems using models based on recurrence relations and differential equations. The platform was developed using Python programming language, Django framework and wide corpus of modules and libraries that supports continuous simulation. The software framework incorporates application programming interface as well, for specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…However, through in-depth research on the Internet of ings, many scholars found that there are still some security problems in the current Internet of ings system [7,8]. e leak door of the network giant Facebook also shows that almost everyone can have no privacy in the network environment [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, through in-depth research on the Internet of ings, many scholars found that there are still some security problems in the current Internet of ings system [7,8]. e leak door of the network giant Facebook also shows that almost everyone can have no privacy in the network environment [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%